Clinical outcome of cardiac resynchronization therapy in patients randomized to an active fixation bipolar left ventricular lead versus a passive quadripolar lead. (2nd June 2021) - Keilegavlen, Havard; Schuster, Peter; Hovstad, Thomas; Faerestrand, Svein
Abstract: Objectives: To compare the clinical outcome of cardiac resynchronization therapy (CRT) in patients receiving a bipolar left ventricular (LV) lead with a side helix for active fixation to the outcome in patients receiving a quadripolar passive fixation LV lead. Design: Sixty-two patients (mean age 72 ± 11 years) were blindly and randomly assigned to the active fixation bipolar lead group ( n  = 31) or to the quadripolar lead group ( n = 31). The LV leads were targeted to the basal LV segment in a vein concordant to the LV segment with the latest mechanical contraction chosen on the basis of preoperative radial strain (RS) echocardiography. Results: At the 6-month follow-up (FU), the reduction in LV end-systolic volume and LV reverse remodelling responder rate, defined as LV end-systolic volume reduction >15%, was 77% in the active fixation group and 83% in the quadripolar group, which was not significantly different. At the 12-month FU, the LV ejection fraction (LVEF) did not differ between the groups. There were no significant differences between the two groups in changes in New York Heart Association (NYHA) functional class or Minnesota Living with Heart Failure Questionnaire score. The occurrence of phrenic nerve stimulation (PNS) was 19% in the active fixation group versus 10% in the quadripolar group ( p =.30), and all cases were resolved by reprogramming the device. All patients were alive at the 12-month FU. There was no device infection. Conclusions: There were no significant differences between the active fixation group of patients and the quadripolar group of patients concerning improvement in echocardiographic parameters or clinical symptoms. ClinicalTrials.gov number, NCT04632472